Nurse-Led Medicines' Monitoring for Patients with Dementia in Care Homes: A Pragmatic Cohort Stepped Wedge Cluster Randomised Trial. - Susan Jordan; Marie Ellenor Gabe-Walters; Alan Watkins; Ioan Humphreys; Louise Newson; Sherrill Snelgrove; Michael S Dennis (PLoS ONE, 2015)
Background People with dementia are susceptible to adverse drug reactions (ADRs). However, they are not always closely monitored for potential problems relating to their medicines: structured nurse-led ADR Profiles have the potential to address this care gap. We aimed to assess the number and nature of clinical problems identified and addressed and changes in prescribing following introduction of nurse-led medicines' monitoring. Design Pragmatic cohort stepped-wedge cluster Randomised Controlled Trial (RCT) of structured nurse-led medicines' monitoring versus usual care. Setting Five UK private sector care homes. Participants 41 service users, taking at least one antipsychotic, antidepressant or anti-epileptic medicine. Intervention Nurses completed the West Wales ADR (WWADR) Profile for Mental Health Medicines with each participant according to trial step. Outcomes Problems addressed and changes in medicines prescribed. Data collection and analysis Information was collected from participants' notes before randomisation and after each of five monthly trial steps. The impact of the Profile on problems found, actions taken and reduction in mental health medicines was explored in multivariate analyses, accounting for data collection step and site. Results Five of 10 sites and 43 of 49 service users approached participated. Profile administration increased the number of problems addressed from a mean of 6.02 [SD 2.92] to 9.86 [4.48], effect size 3.84, 95% CI 2.57-4.11, P <0.001. For example, pain was more likely to be treated (adjusted Odds Ratio [aOR] 3.84, 1.78-8.30), and more patients attended dentists and opticians (aOR 52.76 [11.80-235.90] and 5.12 [1.45-18.03] respectively). Profile use was associated with reduction in mental health medicines (aOR 4.45, 1.15-17.22). Conclusion The WWADR Profile for Mental Health Medicines can improve the quality and safety of care, and warrants further investigation as a strategy to mitigate the known adverse effects of prescribed medicines. Trial registration ISRCTN 48133332.